2003
DOI: 10.1016/s1359-6454(03)00302-1
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of discrete dislocation predictions for near-threshold fatigue crack growth

Abstract: Analyses of the growth of a plane strain crack subject to remote mode I cyclic loading under small scale yielding are carried out using discrete dislocation dynamics. Plastic deformation is modelled through the motion of edge dislocations in an elastic solid with the lattice resistance to dislocation motion, dislocation nucleation, dislocation interaction with obstacles and dislocation annihilation being incorporated through a set of constitutive rules. An irreversible relation is specified between the opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
37
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
2

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 36 publications
1
37
0
Order By: Relevance
“…These discrete dislocation (DD) models have been shown to predict a host of phenomena, such as sizeeffects in yielding, fracture, sliding, indentation, and polycrystals [16][17][18][19][20][21][22], not accounted for in conventional continuum plasticity. In particular, DD studies of fatigue crack growth have been carried out [17,18,[24][25][26][27] that provide insight and guidance into fatigue crack growth problems where continuum plasticity and standard fatigue laws may be inapplicable. Most importantly for our current work is that these DD analyses predict that fatigue crack growth arises naturally under cyclic loading conditions without introducing additional parameters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These discrete dislocation (DD) models have been shown to predict a host of phenomena, such as sizeeffects in yielding, fracture, sliding, indentation, and polycrystals [16][17][18][19][20][21][22], not accounted for in conventional continuum plasticity. In particular, DD studies of fatigue crack growth have been carried out [17,18,[24][25][26][27] that provide insight and guidance into fatigue crack growth problems where continuum plasticity and standard fatigue laws may be inapplicable. Most importantly for our current work is that these DD analyses predict that fatigue crack growth arises naturally under cyclic loading conditions without introducing additional parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly for our current work is that these DD analyses predict that fatigue crack growth arises naturally under cyclic loading conditions without introducing additional parameters. The DD studies of fatigue in single-crystal materials have shown the existence of a threshold, a Paris power-law regime, striations, scaling with material properties and a short-crack regime [17,18,24].…”
Section: Introductionmentioning
confidence: 99%
“…Discrete dislocation (DD) dynamics simulations are not generally plagued by this problem as they can accommodate a much larger spatial domain, while still explicitly modeling every dislocation. However, DD models do not explicitly represent the atomic scale complexities that occur at a crack tip [9][10][11][12][13], and thus cannot illuminate the atomic mechanisms by which a crack tip propagates.…”
Section: Introductionmentioning
confidence: 99%
“…The formulation was presented by Van der Giessen and Needleman in [15] and has been used to solve a variety of two and three dimensional boundary value problems, for example, [16][17][18][19][20][21]. In the calculations here a two dimensional discrete dislocation plasticity formulation is used with the dislocations all of edge character and modeled as line singularities in an isotropic linear elastic solid.…”
mentioning
confidence: 99%
“…However, there are circumstances involving plastic deformation in small volumes where long-range elastic dislocation interactions dominate which permits a wide range of complex phenomena involving plastic deformation to be represented qualitatively, e.g. [4,17,23], and, to a remarkable extent even quantitatively, e.g. [16,24].…”
mentioning
confidence: 99%